Electrochemistry: Aerosol OT/Water System Coupled with Triiodide/Iodide (I3−/I−) Redox Electrolytes for Highly Efficient Dye‐Sensitized Solar Cells (Adv. Energy Mater. 10/2013). Issue 10 (15th October 2013) - Kong, Eui‐Hyun; Lim, Jongchul; Chang, Yong‐June; Yoon, Yeon‐Hee; Park, Taiho; Jang, Hyun Myung
<x xml:space="preserve">Abstract</x> An aerosol OT (AOT; sodium bis(2‐ethylhexyl)sulfosuccinate)/water system coupled with I3−/I− electrolyte enables the control of the concentration of the redox couples through the hydrogen‐bonding association between the AOT and the carboxy group of the dye in dye‐sensitized solar cells (DSCs), as demonstrated by Taiho Park, Hyun Myung Jang, and co‐workers on page 1344. This novel concept provides insight into the regeneration and recombination kinetics and allows for the development of highly efficient DSCs. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>